La conciliación en violencia intrafamiliar cuando no es delito y su Incidencia en los derechos de las partes.Quevedo - Galarza Alvarado, Cruz Elizabeth (2015)
Domestic violence is a reality that we cannot ignore, happening in the country and outside its borders, and in all social strata. With the present investigation it was confirmed that domestic violence exists in the XXI century but could also note that the parties spent the time disgusted repent and want to reconcile the problem, the law does not allow it, because it is so clear to determine that the offender should be tried. Because the country conciliation in family violence are not allowed this reality is confronted with that of neighboring countries, with the result that also protect victims of domestic violence and punish its perpetrators or offenders, but concerned the use alternative means of resolving such conflicts there were no developments. Through surveys and interviews with lawyers in the free exercise, people sentenced for domestic violence, Judges Units of domestic violence and other after data collection, tabulation and analysis of the information obtained it was concluded that Most people do agree with that family violence is one of the main problems affecting society without respect for age, sex or social position, which at the same time the victim of domestic violence should rehabilitate protected the aggressor (a) through psychological therapies, the lack of reconciliation encourages family disintegration, so the question is reliably supported proposal, namely the amendment of sections 641 and 642, paragraph 9 of the Code of Criminal Integral for the use of conciliation as an alternative means for solving family conflicts as a preliminary step to the legal battle, whenever you try not to repeat or that constitute crimes cases.